Amyotrophic lateral sclerosis: improving care with a multidisciplinary approach. - Hogden, A.; Foley, G.; Henderson, R.; James, N.; Aoun, Samar (Dove Medical Press Ltd, 2017)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease, leading to death within an average of 2-3 years. A cure is yet to be found, and a single disease-modifying treatment has had a modest effect in slowing disease progression. Specialized multidisciplinary ALS care has been shown to extend survival and improve patients' quality of life, by providing coordinated interprofessional care that seeks to address the complex needs of this patient group. This review examines the nature of specialized multidisciplinary care in ALS and draws on a broad range of evidence that has shaped current practice. The authors explain how multidisciplinary ALS care is delivered. The existing models of care, the role of palliative care within multidisciplinary ALS care, and the costs of formal and informal care are examined. Critical issues of ALS care are then discussed in the context of the support rendered by multidisciplinary-based care. The authors situate the patient and family as key stakeholders and decision makers in the multidisciplinary care network. Finally, the current challenges to the delivery of coordinated interprofessional care in ALS are explored, and the future of coordinated interprofessional care for people with ALS and their family caregivers is considered.